2019
DOI: 10.1101/736728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motor-mediated clustering at microtubule plus ends facilitates protein transfer to a bio-mimetic cortex

Abstract: Polarized protein distributions at the cortex play an important role in the spatial organization of cells.In S. pombe, growing microtubule ends contribute to the establishment and maintenance of such distributions by delivering specific factors to membrane receptors at the poles of the cell. It is however unclear how microtubule plus-end tracking of proteins favours protein accumulation at the cell cortex compared to proteins arriving directly from the cytoplasm. To address this question, we developed an in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 56 publications
4
9
0
Order By: Relevance
“…6C,D ) (Brunauer and Emmett, 1938; Mitchison, 2020). This is inspired by our experimental observations in guest-host and end-tracking assays, but also supported by other evidence that Tip1 may be able to oligomerize (Chen et al, 2019; Taberner and Dogterom, 2019) and structural data which suggests head-tail interactions between Tip1’s CAP-Gly domain and its C-terminal zinc finger domain (Hayashi et al, 2007; Steinmetz and Akhmanova, 2008). We chose quantitative model parameters where possible (see Materials and Methods and Supplementary Table S2) which also reflect the experimental observation that motors fall off the microtubule end at approximately their stepping rate in the absence of Mal3 ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…6C,D ) (Brunauer and Emmett, 1938; Mitchison, 2020). This is inspired by our experimental observations in guest-host and end-tracking assays, but also supported by other evidence that Tip1 may be able to oligomerize (Chen et al, 2019; Taberner and Dogterom, 2019) and structural data which suggests head-tail interactions between Tip1’s CAP-Gly domain and its C-terminal zinc finger domain (Hayashi et al, 2007; Steinmetz and Akhmanova, 2008). We chose quantitative model parameters where possible (see Materials and Methods and Supplementary Table S2) which also reflect the experimental observation that motors fall off the microtubule end at approximately their stepping rate in the absence of Mal3 ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 83%
“…We found that in vitro molecular crowding agents, such as PEG, drove these proteins into spherical droplets that displayed liquid-like properties: they fused with each other over time, wetted the microtubule surface, transferred from one microtubule to another and were transported by Tea2 motor activity towards microtubule plus-ends. This behaviour shows similarity to the previously observed transfer of end-tracking protein clusters from a microtubule end to a solid barrier (Taberner and Dogterom, 2019), and might be relevant in vivo for the cortical deposition of polarity markers that are crucial for the physiology of fission yeast such as Tea1, Tea4, and Tea3 in addition to Mal3, Tea2, and Tip1 (Behrens and Nurse, 2002; Feierbach et al, 2004; Meadows et al, 2018; Snaith et al, 2005; Snaith and Sawin, 2003).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations